2019
DOI: 10.1002/hast.1050
|View full text |Cite
|
Sign up to set email alerts
|

Developing, Administering, and Scoring the Healthcare Ethics Consultant Certification Examination

Abstract: In November 2018, the practice of health care ethics consultation crossed a major threshold when 138 candidates took the inaugural Healthcare Ethics Consultant Certification Examination. This accomplishment, long in the making, has had and continues to have both advocates and critics. The Healthcare Ethics Consultant Certification Commission, a functionally autonomous body created and funded by the American Society for Bioethics and Humanities, was charged with overseeing creation of the certification process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…There is a relative paucity of evidence regarding any potential associations between HCECs' characteristics, such as the consultants' degree or number of degrees, or their volume of consultative experience, and the quality of their healthcare ethics consultations (Bliss et al, 2016;Magnus 2015). In order to better understand actual practice, in 2016-2017 the American Society for Bioethics and Humanities (ASBH) conducted a HCEC workforce survey (Bruce et al 2019). The survey found that the majority of respondents had bachelor's, but not higher, degrees.…”
Section: Qualificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a relative paucity of evidence regarding any potential associations between HCECs' characteristics, such as the consultants' degree or number of degrees, or their volume of consultative experience, and the quality of their healthcare ethics consultations (Bliss et al, 2016;Magnus 2015). In order to better understand actual practice, in 2016-2017 the American Society for Bioethics and Humanities (ASBH) conducted a HCEC workforce survey (Bruce et al 2019). The survey found that the majority of respondents had bachelor's, but not higher, degrees.…”
Section: Qualificationsmentioning
confidence: 99%
“…HCECs subsequently rated the domains in terms of importance and frequency of occurrence. The number of questions addressing a specific domain are in proportion to that domain's combined importance and frequency (Bruce et al 2019).…”
Section: Examination Scope and Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…CEC is also increasingly implemented in hospitals in European countries such as Germany, the UK and Switzerland (2)(3)(4). To increase prevalence and quality of CEC, recommendations by medical associations (5,6), professional standards (7)(8)(9), training guides and courses (10)(11)(12), certi cation and accreditation programmes (13)(14)(15)(16)) and tools to evaluate CEC (17)(18)(19)) have been developed. There is also now some A total of 664 records were found in the search, 541 without duplicates.…”
Section: Introductionmentioning
confidence: 99%